Effect of packed red blood cell transfusion on the prognosis of patients with upper gastrointestinal bleeding: a retrospective analysis of eICU-CRD v2.0 multicenter critically ill patients database - Zhifa Lv; Yun Zhang (Emergency and Critical Care Medicine)
Abstract. Background. The effects of packed red blood cell (PRBC) transfusion on the prognosis of patients with upper gastrointestinal bleeding (UGIB), particularly on the 30-day mortality rate, are unclear. This study aimed to determine the prognostic influence of PRBC transfusion in patients with UGIB with different hemoglobin (Hb) levels. Methods. The subjects in this study were selected from the Philips Electronic ICU Collaborative Research Database Version 2.0 multicenter critically ill patient database from January 2014 to December 2015. A total of 4689 patients were included in this study. The Hb levels were divided into 3 groups: Hb <6 g/dL (Group 1), 6 g/dL ≤ Hb < 8 g/dL (Group 2), and Hb ≥8 g/dL (Group 3). Based on the administration of PRBC transfusion, each group was subdivided into PRBC and non-PRBC groups. Results. A total of 4689 patients were enrolled in the study, including 825, 2195, and 1669 patients in Groups 1, 2, and 3, respectively. Furthermore, the PRBC and non-PRBC groups consisted of 1847 and 2842 patients, respectively. There was no significant difference in the 30-day mortality rate between Group 1 and Group 2 or between the PRBC and non-PRBC subgroups. In Group 3, the 30-day mortality rate of patients who received transfusion was higher than that of patients who did not (13.29% vs 9.14%, P = 0.029). For the PRBC group, the difference in 30-day mortality rate was not statistically significant among the 3 groups, whereas for the non-PRBC group, the 30-day mortality rate in Group 3 was the lowest, and there was a significant difference among the 3 groups (P = 0.003). There was no significant difference in the subgroup analysis of bleeding at different sites and etiologies. Conclusion. Packed red blood cell transfusion does not improve prognosis or reduce mortality in patients with UGIB but may increase mortality in patients with Hb levels greater than 8 g/dL.